Accounting and Human Resources Information Systems and Their Influence on Increasing The Income of Managers MSME in Indonesia - Anung, Vitriana (International Research & Development for Human Beings (IRDH), 2024)
Micro, small, and medium enterprises (MSMEs) in Indonesia have experienced a significant increase after COVID 19. Reality shows that micro, small, and medium enterprises can help society overcome poverty. However, there are also negative sides that often come from parties such as customers, the government, and so on. The aim of this research is to determine the effect of accounting information systems and human resources on increasing income in MSMEs in Tlogomas and Sumber Sari subdistricts, Malang City, Indonesia. Several things focused on in this research are related to the influence of accounting information systems and human resources on increasing income in two sub-districts, namely Tlogomas Subdistrict and Sumbersari Subdistrict, Malang City. The analytical method used in this research uses a data-based quantitative method, using a sample of 120 MSMEs. The sample was divided into 60 Tlogomas MSME actors and 60 Sumbersari MSME actors used as samples. The results of this research show that the accounting and human resources information systems implemented in the Tlogomas and Sumber Sari sub-districts of Malang City have a positive influence on increasing income.